Diseño arquitectónico de un centro de desarrollo infantil de 0 a 5 años en San José de Chimbo, Bolívar - Calderón Quimi, Stalyn Steven (2024)
San José de Chimbo is one of the many towns in the Ecuadorian Sierra that have a considerable percentage of boys and girls from 0 to 5 years old without help that allows their physical, mental, cognitive and motor development. This town presents a great problem regarding children, the lack of a child development center that is in charge of this entire important stage in the growth of the infant is null, whether due to lack of economic difficulties, lack of commitment, lack of coordination and several aspects that can be mentioned, this generates a need to create an adequate space to ensure the development of the infant. The present work called “Architectural design of a child development center in San José de Chimbo, Bolívar” proposes the implementation of a CDI for these children, offering a solution to the problem caused by the lack of CDI in the area. and around it. To generate the architectural proposal, various factors were analyzed such as the physical environment and conditions when proposing construction projects in an area such as the Andean region where vegetation, ventilation and climate are of vital importance. For this, the different types of materials, styles and strategies that can take advantage of and respect all natural resources, so that a CDI can be designed that provides functional areas, adequate distribution without leaving aside the environment and all environmental resources so that it can respond to the needs of the users who will use them.